2021
DOI: 10.3389/fcvm.2021.758903
|View full text |Cite
|
Sign up to set email alerts
|

Novel SCN5A and GPD1L Variants Identified in Two Unrelated Han-Chinese Patients With Clinically Suspected Brugada Syndrome

Abstract: Brugada syndrome (BrS) is a complexly genetically patterned, rare, malignant, life-threatening arrhythmia disorder. It is autosomal dominant in most cases and characterized by identifiable electrocardiographic patterns, recurrent syncope, nocturnal agonal respiration, and other symptoms, including sudden cardiac death. Over the last 2 decades, a great number of variants have been identified in more than 36 pathogenic or susceptibility genes associated with BrS. The present study used the combined method of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Given that the proband is presented with typical symptoms of CLN2, which follows an autosomal recessive inheritance pattern ( Goebel and Sharp, 1998 ), we speculated that the variant c.230-3C>G might also be pathogenic. To further clarify the pathological significance of the c.230-3C>G variant, we determined the impact of the variant on transcript splicing using the Splicing Reporter Minigene assay ( Hartikainen et al, 1999 ; Yuan et al, 2021 ). The RT-PCR products were analyzed by electrophoresis, and the results showed that the length of the PCR product was shortened in the MT construct ( Figure 3A ), indicating that aberrant splicing occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the proband is presented with typical symptoms of CLN2, which follows an autosomal recessive inheritance pattern ( Goebel and Sharp, 1998 ), we speculated that the variant c.230-3C>G might also be pathogenic. To further clarify the pathological significance of the c.230-3C>G variant, we determined the impact of the variant on transcript splicing using the Splicing Reporter Minigene assay ( Hartikainen et al, 1999 ; Yuan et al, 2021 ). The RT-PCR products were analyzed by electrophoresis, and the results showed that the length of the PCR product was shortened in the MT construct ( Figure 3A ), indicating that aberrant splicing occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of POLR3G resulted in reduced clonal formation of lung cancer cells and increased chemosensitivity of lung cancer cells to paclitaxel (Park et al 2023). GPD1L, which is located on chromosome 3p22.3 (Shrestha et al 2018), catalyze the conversion of sn-glycerol 3-phosphate to glycerone phosphate (Yuan et al 2021) and was found to be involved in more than one type of tumor. For example, Liu et The current study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type and mutant DNA sequences spanning TSC2 gene exons 23–27 and introns 23–26 were amplified from the gDNA of the patient II:2 and introduced into the pMini-SP vector (Beijing Hitrobio Biotechnology Co., Ltd., Beijing, China) (Yuan et al, 2021 ). Human embryonic kidney (HEK) 293T cells were prepared in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum (HyClone, Logan, Utah, USA) at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%